Pengendalian Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode Hiradc di PT. HA Indonesia - Juan Hafizh Al Karim; Asep Erik Nugraha; Wahyudin (Jurnal Serambi Engineering, 2024)
PT. HA Indonesia is a type of Fast-MovingConsumer Goods manufacturer and one of the largest food and beverage companies in Indonesia which produces chili sauce, soy sauce, syrup, and canned food. This research takes a case study in the chili sauce production area. This research is a descriptive study, namely explaining the application of occupational safety and health in the chili sauce production area. The method used is HIRADC (Hazard Identification, Risk Assessment and Determining Control) with the first stage namely identifying hazards, then assessing risks, and the final stage namely controlling hazards. The results of this research are based on hazard identification, there are 24 cases of potential danger, with the risk assessment being that there are 75% or 18 cases of potential danger with low risk (low risk), and as many as 25% or 6 cases of potential danger with severe risk (extreme risk). Suggestions for company owners are to carry out administrative controls, such as: implementing the 5R program, namely clean, tidy, cared for, diligent, and concise; carry out periodic checks on every machine used; pay attention to the facilities and infrastructure in the production area